THE CONCEPT MODEL FOR DELIZIA SELF SERVICE APPLICATION - Fernandus Felix Heriyant; Hari Setiabudi Husni (Asosiasi Dosen Muda Indonesia, 2023)
Delizia Bakery & Cake is a company engaged in the bakery and cake food business. This observation is based on my internship experience at Delizia Bakery & Cake for approximately one year which was carried out on February 1, 2022 to February 13, 2023. In increasing digitization in business processes, providing innovation in digitizing service systems is something that needs to be considered, based on my experience as an intern at the Delizia Bakery & Cake company, I saw where sales of tart orders were usually done manually. By looking at the opportunities of other companies that have implemented digitalization in their business processes, for example McDonald’s, which implements their self service technology in ordering food, I found the idea of an alternative means of selling tarts by making a Self Service Techonlogy tart ordering system. The concept of self service technology is that customers can perform services that have been provided independently and automatically without involving store employees and services provided personally, besides that self service technology is also a new experience and adds to customer interest. and from the results of my research related to the concept of self service technology proposed by me to be used by Delizia Bakery & Cake conceptually approved by stakeholders.